Quantification of Semi-Truck Cab Decontamination - C. Grace Elijah; Cassandra K. Jones; Caitlin Evans; Haley K. Wecker; Charles R. Stark; Jianfa Bai; Elizabeth G. Poulsen-Porter; Allison K. Blomme; Jason C. Woodworth; Chad B. Paulk; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
Evidence suggests that the inside of vehicle cabs used for feed delivery may serve as a potential source for disease, yet there are no standardized protocols or scientific evidence for methods of their disinfection. Therefore, the objective of this project was to evaluate commercially available disinfectants and disinfection application methods against PEDV and PRRSV on various surfaces within semi-truck cabs. Three different surface types common in vehicle cabs (fabric, plastic, and rubber) were cut into 4 × 4 inch coupons and inoculated with either PEDV or PRRSV. Once inoculated, surfaces were placed in one of 3 semi-truck cabs and the disinfectant treatment was applied. Disinfectant treatments were as follows: 1) no-disinfectant, 2) hurricane fumigation with 1:256 dilution of Synergize, 3) hurricane fumigation with 1:64 dilution of Intervention, 4) pump sprayer with 1:256 dilution of Synergize, 5) pump sprayer with 1:64 dilution of Intervention, 6) pump sprayer with 10% bleach, 7) no chemical with 10 hr downtime, and 8) gaseous fumigation over a 10 hr period with water-based chlorine dioxide. Once a disinfectant treatment was applied, the coupons were environmentally swabbed and submitted for qPCR duplex analysis for PEDV and PRRSV. There was a significant disinfectant × surface interaction (P<0.0001) indicating that the disinfectant treatment efficacy differed based on surface. Within rubber surfaces, 10% bleach had a greater Ct value compared to all other treatments (P<0.05), with the exception of Intervention with hurricane fumigation application, which was intermediate. In both fabric and plastic surfaces, there was no evidence (P>0.05) of a difference in Ct value between any of the treatments. Additionally, for the no-disinfectant treatment, the Ct value was greater on fabric surfaces compared to plastic and rubber (P<0.05); fabric was greater than plastic in the Intervention with pump sprayer application treatment (P<0.05), fabric and rubber greater than plastic in the 10% bleach treatment (P<0.05); and fabric greater than plastic and rubber in the 10 hr downtime and gaseous fumigation treatments (P<0.05). There was a significant main effect of disinfectant treatment (P= 0.016), where 10% bleach had a greater Ct value compared to both the control treatment, 10 hr downtime treatment, and Intervention applied using the pump sprayer (P<0.05). There was a main effect of surface (P<0.0001) where rubber had a greater Ct value compared to plastic (P<0.05), and fabric had a greater Ct value compared to both rubber and plastic (P<0.05). Finally, the Ct value for PRRSV was greater than PEDV (P<0.0001) when averaged across all surfaces and disinfectant treatments. In summary, these data highlight that it is important to consider the surface of interest when implementing disinfectant protocols. In general, most disinfectant applications were only able to reduce the quantity of detectable virus, but not completely eliminate it from surface. However, additional research is necessary to understand the viability of residual virus on disinfected surfaces.
Keywords: Decontamination; PEDV; PRRSV; semi-truck cabs